The size effect on fatigue strength of mild steel - Mohd Hafiz Zolkhiflee
Fatigue evaluates the effects of material shape, surface condition, stress level, material size and related factors on fatigue life of metallic materials. This final year project is focused on experimental analysis to compare the effect of a small specimen to that of a larger specimen size of diameter 1mm, 2mm, and 8mm of Mild Steel.